Implications of Socio-Cultural Norms on Individual Behaviour in Elif Shafak’s The Bastard of Istanbul - Rabia Sabir; Muhammad Shehzad Khan (Al Manhal Research Journal, 2024)
Cultural psychology as the name suggests helps us study the effects and changes that a culture has on its people and vice versa. The culture of a country and its people are interdependent and affect each other immensely. Culture moulds the minds of people living under it, their sense of morality and influences responses to a certain situation. Similarly collective wisdom of people continuously updates culture and its traditions. Our intellectual and behavioral characteristics, and culture are interdependent, as they evolve and influence each other simultaneously and this cycle continues. Novels like The Bastard of Istanbul by Elif Shafak (2006) revolves around the dilemma of the struggle between an individual and the effects of society.